The impact of road parameters and the surrounding area on traffic accidents - Šliupas, Tomas (Transport, 2009)
The article analyses the data on road traffic accidents in Lithuanian main and interurban road networks in the years 2002–2006. The road network is divided into 341 road sections. The surrounding area and road parameters of each of the sections are measured. Then, the dependence of traffic accident rate on the parameters is studied and described using linear and multiple regressions. The equations are built using 90% of the available data and tested forecasting traffic accident rate for the rest of 10% of the data comparing the obtained results with the real data. First published online: 27 Oct 2010